Pengaruh Volume Lalulintas Terhadap Tingkat Kebisingan (Studi Kasus Jalan Ahmad Yani Surabaya) - Al-Amin, Rifal; Ikhwanuddin, Ikhwanuddin; Judiono, Judiono (Jurnal Basement : Jurnal Teknik Sipil, 2024)
This study looks at how traffic volume affects road noise levels on  Ahmad Yani, Surabaya. One of the main causes of noise pollution in urban areas is heavy traffic, which can affect quality of life and Health public. The direct measurement method at the location is carried out within seven days of Monday, 4 December to Sunday, 10 December and the data used to collect data on vehicle volume and noise levels throughout the day. The results of data analysis showed a significant positive correlation between traffic volume and noise level; an increase in traffic volume is proportional to an increase in noise level. It is expected that these findings will help local governments make better traffic management policies and strategies to reduce noise pollution to lower noise pollution levels in urban areas. This research also provides suggestions to improving the quality of life of the people of Surabaya through the use of noise reduction technologies and more environmentally friendly infrastructure desing.